Systematic Review tentang Berpikir Komputasi dengan Canva dalam Pendidikan Selama 2018-2024 - Dhevy Kartika Ayu Angkat; Yahfizham (MISTER: Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Computational thinking is the need of the hour. These needs are due to the demands of today's developments. Therefore, it is necessary to carry out regular observations to get updates on improving computational thinking skills, especially in the world of education. Media that is relevant to these needs is Canva, a visual programming media for K-12. A systematic review of computational thinking with Canva has been carried out in this research. In this research, starting from 2018 to 2024, data collection was carried out by reviewing or examining all articles about computational thinking with Canv9 in the field of education published in the 2018-2024 period. The articles used in this research were 7 articles from Google Scholar from national journals with the help of Publish or Perish software. The results of this literature observation indicate that further research is needed regarding methods Times Keywords: Computational Thinking; Knowledge; Canva;